Ganoderma lucidum Pharmacopuncture for the Treatment of Acute Gastric Ulcers in Rats - Jae-Heung Park; Kyung-Jun Jang; Cheol-Hong Kim; Yoo-Hwan Lee; Soo-Jung Lee; Bum-Hoi Kim; Hyun-Min Yoon (Korean Pharmacopuncture Institute, 2014)
Objectives: The gastric ulcer is a common disorder of the stomach and duodenum. The basic physiopathology of a gastric ulcer results from an imbalance between some endogenous aggressive and cytoprotective factors. This study examined whether Ganoderma lucidum pharmacopuncture (GLP) would provide protection against acute gastric ulcers in rats. Methods: Sprague-Dawley rats were divided randomly into 4 groups of 8 rats each: normal, control, normal saline (NP) and GLP groups. The experimental acute gastric ulcer was induced by using an EtOH/HCl solution and the normal group received the same amount of normal saline instead of ethanol. The NP and the GLP groups were treated once with injections of saline and GLP, respectively. Two local acupoints were used: CV12 (中脘) which is the alarm point of the Stomach Meridian, and ST36 (足三里), which is the sea point of the Stomach Meridian. The stomachs from the rats in each group were collected and analyzed for gross appearance and histology. Also, immunohistochemistry staining for BAX, Bcl-2 and TGF-β1 was performed. Results: Histological observations of the gastric lesions in the control group showed comparatively extensive damage of the gastric mucosa and necrotic lesions had penetrated deeply into the mucosa. The lesions were long, hemorrhagic, and confined to the glandular portions. The lesions were measured microscopically by using the clear depth of penetration into the gastric mucosal surface. The length and the width of the ulcer were measured and the inhibition percentage was calculated. Wound healing of the acute gastric ulcer was promoted by using GLP, and significant alterations of indices in gastric mucosa were observed. Such protection was shown by gross appearance, histology and immunohistochemistry staining for BAX, Bcl-2 and TGF-β1. Conclusion: These results suggest that GLP administered at CV12 and ST36 can provide significant protection to the gastric mucosa against an ethanol-induced acute gastric ulcer.